The interdietary relationships between energy, protein and certain amino acids in the nutrition of broiler-type chickens - Brock, Eugene (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. Agric.) -- University of Stellenbosch, 1964.